The Role of nmcR, ampR, and ampD in the Regulation of the Class A Carbapenemase NmcA in Enterobacter ludwigii - Nakano, Ryuichi; Yamada, Yuki; Nakano, Akiyo; Suzuki, Yuki; Saito, Kai; Sakata, Ryuji; Ogawa, Miho; Narita, Kazuya; Kuga, Akio; Suwabe, Akira; Yano, Hisakazu (Frontiers in Microbiology, 2022)
Various carbapenemases have been identified in the Enterobacteriaceae. However, the induction and corresponding regulator genes of carbapenemase NmcA has rarely been detected in the Enterobacter cloacae complex (ECC). The NmcA-positive isolate ECC NR1491 was first detected in Japan in 2013. It was characterized and its induction system elucidated by evaluating its associated regulator genes nmcR, ampD, and ampR. The isolate was highly resistant to all β-lactams except for third generation cephalosporins (3GC). Whole-genome analysis revealed that blaNmcA was located on a novel 29-kb putatively mobile element called EludIMEX-1 inserted into the chromosome. The inducibility of β-lactamase activity by various agents was evaluated. Cefoxitin was confirmed as a strong concentration-independent β-lactamase inducer. In contrast, carbapenems induced β-lactamase in a concentration-dependent manner. All selected 3GC-mutants harboring substitutions on ampD (as ampR and nmcR were unchanged) were highly resistant to 3GC. The ampD mutant strain NR3901 presented with a 700× increase in β-lactamase activity with or without induction. Similar upregulation was also observed for ampC and nmcA. NR1491 (pKU412) was obtained by transforming the ampR mutant (135Asn) clone plasmid whose expression increased by 100×. Like NR3901, it was highly resistant to 3GC. Overexpression of ampC, rather than nmcA, may have accounted for the higher MIC in NR1491. The ampR mutant repressed nmcA despite induction and it remains unclear how it stimulates nmcA transcription via induction. Future experiments should analyze the roles of nmcR mutant strains.